Three Waves of Populism in Latin America - O. V. Varentsova (Vestnik MGIMO-Universiteta, 2014)
Contemporary political regimes in Venezuela and Bolivia led by late Hugo Châvez (now by his successor Nicolas Maduro) and Evo Morales are considered by foreign and Russian scholars as part of the third wave of populism. In the 20th century Latin America already witnessed two waves of populism which coincided with significant political transitions, namely a transition from oligarchy to mass politics accompanied by implementation of import substitution industrialization policies, and a transition from authoritarian rule to democracy during the third wave of democratization which triggered neoliberal reforms inspired by Washington Consensus. This article presents common characteristics of Latin American populist regimes that emerged in different historical periods which help identify the origins as well as distinctive features of Venezuelan and Bolivian political regimes. It is stated that the Châvez and Morales left populist regimes resemble classic populist regimes in that they rely on incendiary anti-establishment discourse. Therefore, left populist regimes are characterized by high levels of polarization as well as weak institutionalization and class or indigenous orientation. Election of left populist leaders may lead to institutional deadlock, uneven playing field and transition to competitive authoritarianism.